Microlithic and Bronze Age camps, 75-26 ft OD, N Carn, Isle of Jura - Mercer, John; Werner, A E A; Binns, R E; Henderson, D M (Proceedings of the Society of Antiquaries of Scotland, 1974)
NR 685939. Mesolithic occupation on a natural platform at the head of N Carn bay included a small L-shaped setting and boulder interpreted as a possible hearth and seat. Charcoal from the setting yielded a radiocarbon date in 6th millennium bc, and associated flint and quartz artefacts included cores, flakes, steeply-trimmed microliths, microburins, scrapers, blades and gravers. Later activity on the site was represented by a fragment of a scale-flaked tool and a 14C-date in earlier 2nd millennium, and also by three barbed-and-tanged points. Pollen evidence is discussed. A R